1964
DOI: 10.1136/gut.5.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen metabolism and excretion in liver disease

Abstract: EDITORIAL SYNOPSIS Raised urinary oestrogen excretion was noted in 16 men and women with liver disease. The study suggests that the increased output of urinary oestrogens was usually due to increased secretion rates of the primary oestrogenic hormones rather than to impaired oestrogen metabolism by the liver.Numerous workers have reported a raised output of urinary oestrogens in men and women with various types of liver disease. Glass, Edmonson, and Soll (1940), Rupp, Cantarow, Rakoff, and Paschkis (1951), Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1965
1965
1985
1985

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…This is most prominent in patients with alcoholic cirrhosis (AC) (4), which is often associated with gynecomastia (5). However, in 54 patients with idiopathic hemochromatosis (IHC), including those with severe liver disease, we did not find gynecomastia (6), in agreement with other surveys (7)(8)(9). This observation suggested that IHC and AC are accompanied by different abnormalities in sex hormone metabolism.…”
supporting
confidence: 92%
“…This is most prominent in patients with alcoholic cirrhosis (AC) (4), which is often associated with gynecomastia (5). However, in 54 patients with idiopathic hemochromatosis (IHC), including those with severe liver disease, we did not find gynecomastia (6), in agreement with other surveys (7)(8)(9). This observation suggested that IHC and AC are accompanied by different abnormalities in sex hormone metabolism.…”
supporting
confidence: 92%
“…Oestrogens could also be involved as a factor in low SM activity in cir¬ rhosis such as abnormal oestrogen metabolism in chronic liver disease (Brown et al 1964;Pentikainem et al 1975) and liver function modification following oestrogen therapy are known. Thus Wiedemann et al (1976) have described a lowering of SM activity and an increase in HGH levels after both acute and chronic oestrogen treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is ascribed to an increased level of transferrin protein and is not accompanied by any demonstrable change in iron absorption (Jacobi et al, 19%; Norrby et a/, 1972). Further studies are needed to establish whether the prolonged therapeutic administration of estrogens at high doses is associated with any signi&cant changes in iron handling, Or whether the high urinary excretion of estrogen in cirrhosis (Brown et al, 1964) is etiologically related to the known tendency of these patients to develop excessive storage iron deposits.…”
Section: Discussionmentioning
confidence: 99%